2021
DOI: 10.1007/s40618-021-01638-w
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome is not associated to an increased risk of low bone mineral density in men at risk for osteoporosis

Abstract: Purpose We have recently demonstrated a significant association between osteoporosis (Op) and metabolic syndrome (MetS) in Caucasian women examined by Dual-energy X-ray absorptiometry (DXA) for suspected Op. This cross-sectional study was performed to evaluate the association between MetS and Op in Caucasian men enrolled in the same geographical area, with identical criteria and in the same time range. Methods Among subjects enrolled in the SIMON study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Testosterone increases the proliferation of osteoblasts and, contextually, reduces pro-apoptotic signaling, through a fine regulation of the protein kinase B, while inhibiting osteoclast formation stimulated by parathyroid hormone [ 68 , 69 ]. Age-related testosterone deficiency is associated with a decrease in bone mineral density (BMD) and an increased risk of fracture [ 70 , 71 , 72 ]. Considering that osteoporosis represents a significant problem in older men and that 30% of all hip fractures occurring in men report increased mortality compared to women, the possibility to maintain testosterone levels within the normal range via TRT is a tempting perspective [ 73 ].…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Testosterone increases the proliferation of osteoblasts and, contextually, reduces pro-apoptotic signaling, through a fine regulation of the protein kinase B, while inhibiting osteoclast formation stimulated by parathyroid hormone [ 68 , 69 ]. Age-related testosterone deficiency is associated with a decrease in bone mineral density (BMD) and an increased risk of fracture [ 70 , 71 , 72 ]. Considering that osteoporosis represents a significant problem in older men and that 30% of all hip fractures occurring in men report increased mortality compared to women, the possibility to maintain testosterone levels within the normal range via TRT is a tempting perspective [ 73 ].…”
Section: Clinical Findingsmentioning
confidence: 99%
“…A similar pattern was also found in other conditions affecting the mineral metabolism, such as osteoporosis, which can be considered the other side of the same process, as well as a risk factor for NL [ 56 ]. The association with metabolic syndrome was found in this case in women but not in men [ 57 , 58 ], so the current degree of adhesion to the MD pattern observed, in Western countries, may be one of the reasons for the growing incidence of metabolic syndrome, osteoporosis, and NL [ 59 ].…”
Section: Discussionmentioning
confidence: 98%
“…Several studies evaluated the risk of osteoporosis in MetS. In 880 Caucasian men with MetS [53], there was no association of MetS with the prevalence of osteoporosis. In contrast, Rhee et al [54] in a Korean population found that MetS was associated with a low occurrence of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%